The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/cryst12121803
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Investigation of the OER Activity for Nickel Phosphite-Based Compositions and Its Morphology-Dependent Fluorescence Properties

Abstract: Herein, we present the investigation of catalytical and fluorescence properties for Ni11(HPO3)8(OH)6 materials obtained through a hydrothermal approach. As part of the constant search for new materials that are both cost effective and electrocatalytically active for the oxygen evolution reaction (OER) in alkaline medium, the present study involves several graphite electrodes modified with Ni11(HPO3)8(OH)6 mixed with reduced graphene oxide (rGO) and carbon black. The experimental results obtained in 0.1 mol L–1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 93 publications
(101 reference statements)
0
2
0
Order By: Relevance
“…Most earth-abundant materials that are OER-active are vulnerable to corrosion due to the acidic environment, while those that are acid-stable are inactive for the OER. Transition metals that have been identified as efficient OER catalysts include divalent cations of metals such as Mn, Fe, Co, and Ni, which exhibit electrocatalytic activity in the following order, Mn 2+ < Fe 2+ < Co 2+ < Ni 2+ [72]; this is due to a weakening of the metal-oxygen bond, resulting in reduced corrosion resistance [66]. Cations with high valence states are suggested as the active site for the OER, for example, Fe 3+ , Fe 4+ , Co 3+ , Co 4+ , or Mn 3+ , since the high oxidation states could serve as an electron acceptor [40].…”
Section: Single-component and Binary-component Electrocatalysts And E...mentioning
confidence: 99%
“…Most earth-abundant materials that are OER-active are vulnerable to corrosion due to the acidic environment, while those that are acid-stable are inactive for the OER. Transition metals that have been identified as efficient OER catalysts include divalent cations of metals such as Mn, Fe, Co, and Ni, which exhibit electrocatalytic activity in the following order, Mn 2+ < Fe 2+ < Co 2+ < Ni 2+ [72]; this is due to a weakening of the metal-oxygen bond, resulting in reduced corrosion resistance [66]. Cations with high valence states are suggested as the active site for the OER, for example, Fe 3+ , Fe 4+ , Co 3+ , Co 4+ , or Mn 3+ , since the high oxidation states could serve as an electron acceptor [40].…”
Section: Single-component and Binary-component Electrocatalysts And E...mentioning
confidence: 99%
“…It evaluates the HER electrocatalytic properties in an alkaline medium of graphite electrodes modified with combinations between a transition metal-based compound-Ni 11 (HPO 3 ) 8 (OH) 6 -and each member from a series of four metalfree porphyrins. Previous reports have shown that nickel phosphite (NiPh) exhibits watersplitting catalytic activity [35][36][37][38]. As for the porphyrins, namely 5-(4-pyridyl)-10,15,20tris(4-phenoxyphenyl)porphyrin (P1), 5,10,15,20-tetrakis(4-allyloxyphenyl)porphyrin (P2), 5,10,15,20-tetrakis(p-tolyl)porphyrin (P3) and 5,10,15,20-tetrakis(4-methoxyphenyl)porphyrin (P4), they have been the focus of various studies reported by Fagadar et al [23,[39][40][41][42][43][44][45][46][47][48][49][50][51][52][53], during which they were thoroughly characterized by physical-chemical and electrochemical methods, and their potential applications were evidenced together with their HER and OER electrocatalytic activity in basic medium.…”
Section: Introductionmentioning
confidence: 99%